2022
DOI: 10.3390/foods11111601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homogenization Modified Rice Protein on the Pasting Properties of Rice Starch

Abstract: Modification of plant-based protein for promoting wide applications is of interest to the food industry. Rice protein from rice residues was modified by homogenization, and its effect on pasting properties (including gelatinization and rheology) of rice starch was investigated. The results showed that homogenization could significantly decrease the particle size of rice protein and increase their water holding capacity without changing their band distribution in SDS-PAGE. With the addition of protein/homogeniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Of all the materials sampled, both rice compositions have the least difference in viscosity levels. Shear-thinning viscosity curves for rice protein were also reflected in the literature, even with different sample preparation techniques [88,89]. This shear-thinning flow behavior suggests that the rice protein acts as a pseudoplastic fluid [88].…”
Section: Brown Rice Protein Viscosity Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Of all the materials sampled, both rice compositions have the least difference in viscosity levels. Shear-thinning viscosity curves for rice protein were also reflected in the literature, even with different sample preparation techniques [88,89]. This shear-thinning flow behavior suggests that the rice protein acts as a pseudoplastic fluid [88].…”
Section: Brown Rice Protein Viscosity Resultsmentioning
confidence: 75%
“…Other compounds within the commercial rice protein, such as carbohydrates, may also interfere with the bonding behavior. A study involving homogenized rice protein and starch samples at various concentrations also produced results where the addition of protein decreased viscosity [88]. Since the rice protein used to make compositions A and B was commercially obtained, it is not unreasonable to assume that possible previous treatments, such as homogenization, may have taken place, which would influence the viscosity.…”
Section: Brown Rice Protein Viscosity Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocheme et al [38] reported that the pasting attributes decreased as carbohydrates decreased. Protein affects the pasting properties by interacting with starch molecules and modifying their gelatinization behavior [40]. For example, in SCF, using the Brabender Viscograph-E device, the SF composite with wheat flour in different proportions sorghum: wheat 10:90, 20:80, 30:70, the maximum viscosity was high in the higher percentage of replacement of wheat flour so that the replacement sample by 30% decreased at a low level of 505.00 BU [14].…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…Ocheme et al [16] reported that the pasting attributes decreased as carbohydrates decreased. Protein affects the pasting properties by interacting with starch molecules and modifying their gelatinization behavior [18].…”
Section: Introductionmentioning
confidence: 99%